Why fiction matters in contemporary China - Wang, Dewei (Brandeis University Press, 2020)
"Contemporary discussions of China tend to focus on politics and economics, giving Chinese culture little if any attention. Why Fiction Matters in Contemporary China offers a corrective, revealing the crucial role that fiction plays in helping contemporary Chinese citizens understand themselves and their nation. Where history fails to address the consequences of man-made and natural atrocities, David Der-wei Wang argues, fiction arises to bear witness to the immemorial and unforeseeable. Beginning by examining President Xi Jinping's call in 2013 to "tell the good China story," Wang illuminates how contemporary Chinese cultural politics have taken a "fictional turn," which can trace its genealogy to early modern times. He does so by addressing a series of discourses by critics within China, including Liang Qichao, Lu Xun, and Shen Congwen, as well as critics from the West such as Arendt, Benjamin, and Deleuze. Wang highlights the variety and vitality of fictional works from China as well as the larger Sinophone world, ranging from science fiction to political allegory, erotic escapade to utopia and dystopia. The result is an insightful account of contemporary China, one that affords countless new insights and avenues for understanding"--